Anti-inflammatory effect of the mixture of Ageratum conyzoides L. extract and eggshell membrane hydrolysates and in silico active compound predictions - Suci Nar Vikasari; Elin Yulinah Sukandar; Tri Suciati; I Ketut Adnyana (GarVal Editorial Ltda., 2024)
Context: Ageratum conyzoides L. and eggshell membrane have the potential to be used as medicine. The independent use of A. conyzoides extract or eggshell membrane hydrolysates independently as a natural medicine has been widely known, but the mixture of the two as an anti-inflammatory has not been studied. Aims: To evaluate both the in vivo and in vitro anti-inflammatory effects of A. conyzoides extract and eggshell membrane hydrolysates, independently and in combination. In silico testing was conducted to identify chemicals that have a key role in inflammation signaling pathways. Methods: The chronic anti-inflammatory effects of A. conyzoides extract and eggshell membrane hydrolysates were evaluated on cotton pellet-induced rats using diclofenac-Na as a control. In vitro anti-inflammatory effects were studied via protein denaturation, membrane stability, and antiprotease activity. Furthermore, molecular docking was performed on the p38-MAPK signaling pathway using compounds found in A. conyzoides extract and eggshell membrane hydrolysates. Results: A. conyzoides extract and eggshell membrane hydrolysates given separately or in combination can inhibit the formation of exudates and granulomas. Molecular docking simulations showed that the metabolites in the extract and hydrolysate interact with p38-MAPK. Nobiletin in the extract is the potential metabolite that interacts with the p38-MAPK receptor with a free energy of binding and inhibition constant of -8.92 kcal/mol and 260.80 nM. Amino acids in the hydrolysates showed weaker interactions compared to the compound in the extract. Conclusions: A. conyzoides extract and eggshell membrane hydrolysates work additively to inhibit the severity of chronic inflammation.